Análisis sociosemántico a la narrativa de los adolescentes (2022)
Eng: In this paper, a brief socio-semantic analysis of the jargon recorded in the narratives of adolescents in grade 10 and 11 of the Normal School of Socha is carried out, in order to know the modifications that they give to the language not only inside but also outside of the school and how these variations are involved in creating bonds of friendship, acceptance and inclusion with their classmates. For this purpose, it is described the way in which adolescent jargon is used in environments like family, friends and teachers, and it identifies factors such as gender and the fact of growing up in this town in Boyacá state that help the creation of these words.